Efficacy of verbenone and a blend of verbenone and nonhost volatiles for protecting lodgepole pine from mountain pine beetle (Coleoptera: Curculionidae). (3rd July 2020) - Fettig, Christopher J.; Munson, A. Steven
Abstract: Significant research has been devoted to the development of semiochemical repellents for mountain pine beetle Dendroctonus ponderosae Hopkins. Several formulations of the beetle's antiaggregation pheromone verbenone (4, 6, 6‐trimethylbicyclo[3.1.1]hept‐3‐en‐2‐one) are registered to protect pine trees and stands. We compared the efficacy of verbenone and Verbenone Plus for protecting individual lodgepole pine Pinus contorta Dougl. ex Loud. and small stands of P. contorta from mortality attributed to D. ponderosae . Verbenone Plus is a blend of semiochemicals [(−)‐verbenone, acetophenone, and ( E )‐2‐hexen‐1‐ol + ( Z )‐2‐hexen‐1‐ol] originally developed to inhibit aggregation of western pine beetle D. brevicomis LeConte. It is the only effective semiochemical repellent that protects ponderosa pine P. ponderosa Dougl. ex Laws. from mortality attributed to D. brevicomis, but has yet to be registered or commercialized. Both verbenone and Verbenone Plus were effective for protecting individual P. contorta and small stands of P. contorta from mortality attributed to D. ponderosae . Verbenone alone was as effective as Verbenone Plus. An obstacle to the broader use of semiochemical repellents for the management of bark beetles is the relatively high cost and specificity of the semiochemicals involved. A semiochemical repellent with efficacy across multiple bark beetle species and hosts, such as Verbenone Plus, would be desirable, assuming the additional components are not cost‐prohibitive or limit registration.